A facile method to fabricate durable super‐hydrophobic cotton fabric. Issue 1 (17th May 2019) - Li, Junyu; Wu, Xi; Jiang, Peiqing; Li, Linfeng; He, Jiahao; Xu, Weilin; Li, Wenbin
Abstract : This article presents the fabrication of super‐hydrophobic cotton fabric using titanium dioxide nanoparticles and tetraethyl orthosilicate, alongside control samples modified by 1 H, 1 H, 2 H, 2 H ‐perfluorooctyltriethoxysilane. The samples were analyzed using scanning electron microscopy and Fourier transform infrared spectrometry, and then, the water contact angles were measured. Moreover, the durability of the hydrophobic surface was examined by measuring the abrasion resistance and laundering durability. For the tetraethyl orthosilicate‐treated fabric, the water contact angle reached 150.3°, whereas that for the 1 H, 1 H, 2 H, 2 H ‐perfluorooctyltriethoxysilane‐treated fabric was 154.1°. After 300 abrasion cycles (or 40 min of laundering), the water contact angles of cotton fabrics treated with a 20% tetraethyl orthosilicate treatment solution dropped by 6.67% (or 2.86%). Therefore, hydrophobic cotton fabrics can be obtained via treatment with tetraethyl orthosilicate solution, which is more environmentally friendly than that obtained via fluorosilanes such as 1 H, 1 H, 2 H, 2 H ‐perfluorooctyltriethoxysilane. J. VINYL ADDIT. TECHNOL., 26:3–9, 2020. © 2019 Society of Plastics Engineers